2016
DOI: 10.7567/jjap.55.06gf01
|View full text |Cite
|
Sign up to set email alerts
|

Properties of single-layer MoS2 film fabricated by combination of sputtering deposition and post deposition sulfurization annealing using (t-C4H9)2S2

Abstract: The fabrication of a high-quality single-layer MoS2 film was achieved at a sufficiently low temperature of 500 °C by the combination of sputtering deposition and post deposition sulfurization annealing. Fabrication only by sputtering produces unintentionally sulfur-deficient nonstoichiometric films with poor crystalline quality in nature, making it difficult to fabricate atomically thin sputtered MoS2 films, especially with a single layer. From the results of the sulfurization annealing, sulfur deficiencies in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 26 publications
1
24
0
Order By: Relevance
“…Single and few-layer MoS 2 can be prepared by a number of methods, including micromechanical exfoliation, , chemical vapor deposition, ,− physical vapor deposition, , ultrasonic-assisted liquid exfoliation, , Li-intercalation exfoliation, ,, hydrothermal synthesis, chemical and electrochemical processes, , thermolysis of the precursors such as alkyldiammonium tetrathiomolybdates, sulfurization of molybdenum trioxide (MoO 3 ) and Mo, sulfurization of preannealed Mo foil, and radio frequency (RF) sputtering method. Liu et al reported a new synthetic method for preparing large-area MoS 2 thin layers on sapphire and silicon substrates from ammonium thiomolybdate solution in the presence of argon (Ar) and sulfur (S) at very high annealing temperatures. In the first step, the precursor ammonium thiomolybdate [(NH 4 ) 2 MoS 4 ] was dip-coated on either sapphire or SiO 2 /Si substrate, followed by annealing at 500 °C for 1 h in a gas mixture of argon/hydrogen (Ar/H 2 ).…”
Section: Transition Metal Dichalcogenides (Tmds) and Molybdenum Disul...mentioning
confidence: 99%
“…Single and few-layer MoS 2 can be prepared by a number of methods, including micromechanical exfoliation, , chemical vapor deposition, ,− physical vapor deposition, , ultrasonic-assisted liquid exfoliation, , Li-intercalation exfoliation, ,, hydrothermal synthesis, chemical and electrochemical processes, , thermolysis of the precursors such as alkyldiammonium tetrathiomolybdates, sulfurization of molybdenum trioxide (MoO 3 ) and Mo, sulfurization of preannealed Mo foil, and radio frequency (RF) sputtering method. Liu et al reported a new synthetic method for preparing large-area MoS 2 thin layers on sapphire and silicon substrates from ammonium thiomolybdate solution in the presence of argon (Ar) and sulfur (S) at very high annealing temperatures. In the first step, the precursor ammonium thiomolybdate [(NH 4 ) 2 MoS 4 ] was dip-coated on either sapphire or SiO 2 /Si substrate, followed by annealing at 500 °C for 1 h in a gas mixture of argon/hydrogen (Ar/H 2 ).…”
Section: Transition Metal Dichalcogenides (Tmds) and Molybdenum Disul...mentioning
confidence: 99%
“…On the other hand, the EDS revealed that the S/Sn ratio of the as-deposited film was about 1.2, which is far from the stoichiometric ratio of SnS 2 . The deficiency of sulfur content tends to occur among metal chalcogenides, and it could be significant for sputtering processes under no sulfur source supply. , This is probably attributed to a relatively high vapor pressure of sulfur. Although the S/Sn ratio was slightly improved to 1.3 after the H 2 S annealing, it still deviates from the stoichiometric composition.…”
Section: Resultsmentioning
confidence: 99%
“…However, these techniques are not scalable as sputtering technique. On the other hand, sputtering technique demonstrates continuous film of amorphous and non-stoichiometric MoS2 with sulfur vacancies [33]. This could be due to the difference in sputtering yield and vapour pressure of Mo and S atoms.…”
Section: Introductionmentioning
confidence: 99%
“…Sputtering technique for the fabrication of mono-to few-layer MoS2 follows two methods in general; (i) sputter deposition of Mo thin film followed by converting it into crystalline MoS2 by sulfurization process [1,33,[39][40][41][42] , (ii) sputter deposition of amorphous MoS2 thin film (with S deficiency) followed by sulfurization process to convert amorphous MoS2 into crystalline MoS2 [35,36,43,44]. From this, it is clear that the sulfurization is an essential process independent of depositing Mo or MoS2 for fabricating crystalline MoS2 film using sputtering technique.…”
Section: Introductionmentioning
confidence: 99%